(untitled) (The Insight, 2025)
Background: Pediatric outpatient departments (OPDs) are critical for early diagnosis and management of childhood illnesses. Understanding the clinicopathological profile of pediatric outpatients is essential for guiding effective healthcare strategies and improving child health outcomes in resource-limited settings. Aim of the study: To analyze the clinicopathological profile of pediatric outpatients at Bangladesh Shishu Hospital & Institute, Dhaka, identifying prevalent diseases, clinical presentations, laboratory findings, nutritional status, and outcomes. Methods & Matrials: A hospital-based cross-sectional study was conducted over six months, enrolling 310 children below 15 years attending the pediatric OPD. Demographic data, clinical complaints, provisional diagnoses, laboratory findings, and nutritional status were recorded. Outcomes were categorized as conservative management, hospital admission, or specialist referral. Data were analyzed using SPSS version 26, with p≤0.05 considered statistically significant. Result: The mean age was 5.41 ± 3.97 years, with 55.5% males and 62.6% from urban areas. Fever (41.3%) and cough/cold (32.9%) were the most common complaints. Respiratory tract infections (36.1%) and gastrointestinal disorders (25.2%) predominated. Laboratory abnormalities were observed in hemoglobin (43.2%), WBC count (32.9%), and ESR (38.1%). Nutritional assessment revealed 41.3% of children were underweight, stunted, or wasted. Most children (69.0%) were managed conservatively, while 23.2% required admission. Conclusion: Respiratory and gastrointestinal illnesses remain the leading causes of pediatric outpatient visits, with a substantial burden of malnutrition and laboratory abnormalities. These findings emphasize the need for targeted preventive, diagnostic, and management strategies to optimize pediatric healthcare outcomes in Bangladesh.